Designing Educational Game through Android for Senior High School in Second Grade - Luluk Choirun Nisak Nur; Insaanu Mu'minaati; Nurul Afidah (SCHOOLAR: Social and Literature Study in Education, 2021)
In teaching and learning process, learning media is one of vital tool as technology facility in the education sector, create many new opportunities to enhance the learning experience of students at all levels of education, one of them is in High School education. Educating them is very interesting and very different, because it requires creativity and logical thinking skills and always follows the development of the digitalization era. Therefore, the researchers aim to design English learning media for class XI students in Senior High School that their needs. The purpose of the research is to designing an Android-based educational game media for English subjects in reading and writing skills in High School to help students make it easier to learn English and to find out how is appropriate the educational game media. The researchers used the Research and Development method which is adapted from the development of ADDIE. Namely of this learning media is Senior English Game (SEG). SEG is an application designed to help students enhance their interest in learning English especially on reading and writing skills. The result of this research indicate that 1) the results of the media expert score are 4.60. 2) The results of the material expert score 4.3. 3) The result of the field test score is 4.43. Based on the results above, the researchers concluded that the Senior English Game (SEG) media suitable to used in learning English.